Improving English University Students’ Speaking Skill Through Effortless English Movie Technique - Dian Purnama Sari; Salmi Tri Apriani (Politeknik Negeri Padang, 2020)
The aim of this article was to explain how to implement Effortless English Movie Technique in order to improve students’ English speaking skill. Effortless English Movie is a six-day implementation technique that has different instructions for each day. It was a library research since the data are taken by gathering information from books and journals. However, the researchers also did pre-liminary observation to see the students’ perception toward the learning technique at university level to get a better comprehension about the real situation in learning process. The researchers, then, adapted the theory of the Effortless English Movie by A.J. Hoge with the real situation, so it can be used by the teachers well into their classrooms. This technique leads learners to focus on listening to be familiar with English conversation or dialogue, and continue to the speaking section to practice their pronunciation with the movie that has been chosen by the teacher. By using repetition strategy to practice the speaking skill, this technique focuses on speaking like a native speaker with an amusing way. Therefore, Effortless English Movie Technique is an optional easy and enjoyable technique that helps students a lot in learning to communicate fluently and accurately. The researchers hope that this article is useful for the readers, students, teachers, and next researchers in giving information about improving speaking skill. The researchers also expect that this technique can be one of the most favorite techniques that teachers use in classroom for English lesson, especially speaking skill.